2009
DOI: 10.1590/s1676-06032009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of climbers in seasonal semideciduous forest fragments of Southeastern Brazil

Abstract: In this study we evaluated floristic composition patterns of communities of climbers within ten inventories carried out in semideciduous forest fragments of southeastern Brazil. One of the inventories is original, being carried out for the present study in Ribeirão Cachoeira forest, Campinas, São Paulo State, Southeastern Brazil. This inventory was then pooled together to other nine climbers' inventories made in other forests of Southeastern Brazil to form a data base, which was examined regarding species rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
1
21
0
11
Order By: Relevance
“…When analyzing climbing mechanisms combining them in four major groups (joining stem twiner species with petiole twiner and secondary shoot twiner; tendril species with clasp tendril and adhesive tendril species; scrambler species with hook/spine species; and the adherent root species), as commonly seen in studies that classify the species' climbing mechanisms (e.g. Santos et al 2009), the Fisher's exact test showed a significant result (P = 0.02). …”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…When analyzing climbing mechanisms combining them in four major groups (joining stem twiner species with petiole twiner and secondary shoot twiner; tendril species with clasp tendril and adhesive tendril species; scrambler species with hook/spine species; and the adherent root species), as commonly seen in studies that classify the species' climbing mechanisms (e.g. Santos et al 2009), the Fisher's exact test showed a significant result (P = 0.02). …”
Section: Resultsmentioning
confidence: 79%
“…Our sites comparison is more detailed in relation to forest types, showing that the Semideciduous forests that are geographically close and present a mixture of floristic contingents of different origins (Waechter 2002) are more similar to Deciduous forests than Araucaria/Atlantic forests. It is noteworthy, as cited by Santos et al (2009) that any species richness comparison between these surveys should be done with some caution, since they differ in sampled area and time effort and some studies may be underestimating the real richness of the study areas.…”
Section: Discussionmentioning
confidence: 99%
“…Elas constituem um importante componente da estrutura da floresta tropical, com mais de 25% da diversidade de espécies lenhosas (Gentry 1991, Addo-Fourdjour 2009. Particularmente na Floresta Estacional Semidecidual, onde já foram encontradas até 148 espécies de trepadeiras (Udulutsch et al 2004), podendo corresponder a 52,5% da riqueza de espécies lenhosas (Santos et al 2009). …”
Section: Introductionunclassified
“…A alta diversidade de plantas de hábito trepador em florestas tropicais, particularmente aquelas fragmentadas ou perturbadas, tem chamado a atenção por constituírem um componente que contribui significativamente na composição e estrutura das sinúsias fl orestais (Barros et al 2009, Santos et al 2009, Rubim et al 2010.…”
Section: Introductionunclassified
“…No Brasil, os trabalhos para essa forma de vida abordam, principalmente, estudos fl orísticos (Morellato & Leitão Filho 1996, Udulutsch et al 2004, Rezende & Ranga 2005, Tibiriçá et al 2006, Santos et al 2009, Villagra & Romaniuc Neto 2010 e, com menor frequência, estudos ecológicos (Lombardi et al 1999, Hora & Soares 2002.…”
Section: Introductionunclassified